Analysis of mass sports development in Russia and Europe - Enchenko, I.; Myakonkov, V.; Egorova, N. (BIO Web of Conferences, 2020)
In this article, the authors consider the development of mass sports in Russia and Europe, study such indicators of the development of physical culture as the number of systematically engaged in physical activity, the age of the people engaged in sports, preferred places for physical training, as well as the level of satisfaction with the conditions for physical activity in the community. The authors also give examples of projects for the development of physical activity in Russia and Europe.